The role of parent–child communication on Chinese rural left-behind children’s educational expectation: a moderated mediation analysis - Jia Zhuang; Jacky C. K. Ng; Qiaobing Wu (Humanities & Social Sciences Communications)
Abstract Parents are the most intimate and proximal influences on a child’s development. Migration-induced parental absence in rural China might pose a considerable threat to the educational development of left-behind children because of insufficient parent–child communication. Despite growing scholarly attention, we know little of the effect of parental migration on either parent–child communication or the educational expectations of rural students of different left-behind status (i.e., left behind by two parents; left behind by one parent; or living with both parents). Drawing upon the longitudinal data of the China Education Panel Survey (N = 2275), this study used a two-step path analysis to examine the interrelations among Chinese rural students’ left-behind status, received parent–child communication, and educational expectations. Parental migration negatively affected parent–child communication, and parent–child communication was positively correlated with rural children’s educational expectations. In addition, left-behind status moderated the association between parent–child communication and rural students’ educational expectations. We conclude that rural students’ left-behind status affects their educational expectations through parent–child communication. These results add to the existing understanding of how parental migration affects rural children’s educational expectations and indicates the protective effect of parent–child communication.